Pengembangan LKPD Berbasis Etnomatika pada Materi Bangun Datar Menggunakan Model RME untuk Meningkatkan Minat Belajar Siswa SD - Novia Wulandari Damanik; Ahmad Landong; Selly Pratiwi; Nana Apriyana; Muhammad Nur Fadlan; Ananda Rika Azhari; Desi Ratna Sambo; Siti Anisah; Septi Annasiah Hasibuan; Henvy Yulifasari Lingga; Gusti Nawang Sari; Ysril Liza Andini (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This research aims to develop ethnomathematics-based Student Worksheets (LKPD) on flat shapes using the Realistic Mathematics Education (RME) model to increase the learning interest of fourth-grade elementary school students. The research method used is Research and Development, with the subjects being fourth-grade students of SD Negeri 064955 and the object being the developed LKPD. The results of trials on 20 students showed an average score of 3.75, which is categorized as very practical, with students feeling happy because the material is presented in familiar cultural stories and fun activities. The responses of teachers and students to the development of this LKPD were very positive, the validity level of the LKPD was very high, and it was effective in increasing students' learning interest, so this LKPD is suitable for use as an innovative learning medium in elementary schools.